2008
DOI: 10.2308/accr.2008.83.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Surprises that Motivate Analysts to Reduce Average Forecast Error

Abstract: Large earnings surprises and negative earnings surprises represent more egregious errors in analysts' earnings forecasts. We find evidence consistent with our expectation that egregious forecast errors motivate analysts to work harder to develop or acquire relatively more private information in an effort to avoid future forecasting failures. Specifically, we find that after large or negative earnings surprises there is a greater reduction in the error in individual analysts' forecasts of future earnings, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 35 publications
6
74
0
Order By: Relevance
“…We control for a bank's financial strength by including its level of Tier 1 capital (Tier 1) and for bank type using a dummy variably that is equal to 1 if the bank is a financial holding company and 0 if it is a bank holding company (Financial). We also control for a bank's size (Size) using the natural logarithm of total assets (Barron et al 2008) and bank's performance using the return on equity ratio (ROE). To control for earnings surprises, we include ΔEarnings , which is measured as the earnings at time t minus earning at time t-1 over earning at time t-1.…”
Section: Control Variablesmentioning
confidence: 99%
“…We control for a bank's financial strength by including its level of Tier 1 capital (Tier 1) and for bank type using a dummy variably that is equal to 1 if the bank is a financial holding company and 0 if it is a bank holding company (Financial). We also control for a bank's size (Size) using the natural logarithm of total assets (Barron et al 2008) and bank's performance using the return on equity ratio (ROE). To control for earnings surprises, we include ΔEarnings , which is measured as the earnings at time t minus earning at time t-1 over earning at time t-1.…”
Section: Control Variablesmentioning
confidence: 99%
“…The authors interpreted these results to mean that earnings announcements play the role of triggering the production of private information by sophisticated users such as analysts. Barron et al(2008) investigated the effect of large earnings surprises and negative earnings surprises on analysts' reliance on common information. Their analyses showed that after a large earnings surprise or a negative earnings surprise, analysts' forecast bias is substantially reduced and their reliance on private information increases.…”
Section: A Backgroundmentioning
confidence: 99%
“…To test Hypothesis 1, we estimate the following OLS regression: Equation (6) is based on Barron et al(2008). The dependent variable, ρ , refers to the analyst's reliance on common information.…”
Section: Empirical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to the extent that these firm-specific factors reduce the quality (or precision) of commonly available information, investors' demand for analyst-provided information is expected to shift outward, thereby increasing equilibrium supply. Under the assumption that an analyst is interested in maximizing her expected utility, she will invest effort to generate idiosyncratic information to satisfy investors' demand, up to the point where her marginal costs of generating idiosyncratic information equal the marginal benefits of providing such information to investors (see Barron, Byard, & Yu, 2008;Barth, Kasznik, & McNichols, 2001;Das, Levine, & Sivaramakrishnan, 1998;Djatej, Gao, Sarikas, & Senteney, 2009;O'Brien & Bhushan, 1990). The next section discusses prior studies examining the relationship between corporate disclosure and analysts' efforts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%